Phenological of Quercus coccifera L. trees in Al-Jabel Al-Akhder region, Libya - Amel Fathi Tashani; Saleh Attia Bogarsa; Saad Mohamed Saad (African Journal of Advanced Pure and Applied Sciences, 2025)
This study examined how climatic and soil factors influenced the phenological of Quercus coccifera L. at different altitudes Lamlouda, Arqoub Al-Abyad, and Sidi Khaled in Al-Jabel Al-Akhder region, Libya during 2022–2023. In 2022, warmer temperatures and higher rainfall in Lamlouda correlated with earlier bud emergence (25 Feb) and acorn ripening (4 Oct). Conversely, cooler and drier conditions in Arqoub Al-Abyad were associated with delayed bud break (8 Mar) and prolonged flowering (up to 12 May in 2023). Relative humidity influenced flowering duration, with higher values in 2023 at Lamlouda coinciding with compact flowering periods, while moderate humidity in Arqoub Al-Abyad extended flowering. Solar radiation, though similar between sites, was higher in 2023 and may have accelerated bud and fruit development across all locations. Soil properties also played a role: higher organic matter in Sidi Khaled coincided with later bud emergence but balanced flowering, while elevated salinity, phosphorus, and nitrogen in Arqoub Al-Abyad were linked to extended reproductive phases but delayed fruit maturation. Higher potassium in Lamlouda corresponded with earlier and faster fruit ripening. These findings suggest that warmer, wetter conditions combined with favorable soil fertility (high potassium and moderate salinity) promote earlier phenological events, whereas cooler, drier climates with high salinity and nutrient imbalance delay developmental stages but may extend flowering periods Integrated management of climate adaptation strategies and soil nutrient optimization is recommended to enhance productivity and reproductive success of Q. coccifera in variable Mediterranean environments.